The European Lead Factory: A Blueprint for Public–Private Partnerships in Early Drug Discovery - Karawajczyk, Anna; Orrling, Kristina M.; de Vlieger, Jon S. B.; Rijnders, Ton; Tzalis, Dimitrios (Frontiers in Medicine, 2017)
The European Lead Factory (ELF) is a public–private partnership (PPP) that provides researchers in Europe with a unique platform for translation of innovative biology and chemistry into high quality starting points for drug discovery. It combines an exceptional collection of small molecules, high throughput screening infrastructure and hit follow-up capabilities to advance research projects from both private companies and publicly funded researchers. By active interactions with the wider European life science community, ELF connects and unites bright ideas, talent, and experience from several disciplines. As a result, ELF is a unique, collaborative lead generation engine that has so far resulted in >4500 hit compounds with a defined biological activity from 83 successfully completed high throughput screening and hit evaluation campaigns. The PPP has also produced more than 120,000 novel innovative library compounds that complement the 327,000 compounds contributed by the participating pharmaceutical companies. Intrinsic to its setup, ELF enables breakthroughs in areas with unmet medical and societal needs, where no individual entity would be able to create a comparable impact in such a short time.